Gaya Bahasa Pada Lirik Lagu Spirits Of The Sea Karya Kenshi Yonezu - Zaki Ainul Fadli; Dewi Kusmiati (KIRYOKU, 2020)
(Title: Stylistics on Song Lyrics Spirits of the Sea by Kenshi Yonezu) Lyrics of the song are an outpouring of the author's personal feelings and contain various meanings based on the style of language used. The style of language in a literary work is known as the 'stylistics'. In this regard, this research trying to find out the stylistic elements (language style) contained in the lyrics of Spirits of the Sea by Kenshi Yonezu. The theory used is the style theory by Gorys Keraf. In conducting this research, the author uses qualitative methods. Data processing techniques used are literature review and analysis techniques. Data obtained by reading the lyrics of the song Spirits of the Sea by Kenshi Yonezu. Through library research methods and analysis techniques, the results and conclusions obtained in the form of qualitative data is description and interpretation, namely the style of language based on the choice of words used and the style of language based on the sentence structure in the lyrics. Besides, there are several types of language styles based on the direct or indirect meaning in the lyrics of the song Spirits of the Sea by Kenshi Yonezu such as personification, hyperbole, etc.